Watershed : A New Era of Water Governance in China — Synthesis Report - World Bank Group (World Bank, Washington, DC, 2019)
This report represents a synthesis of joint research conducted by the Development Research Center of the State Council of the People's Republic of China (DRC) and the World Bank. Building on the track record of research collaboration between the World Bank and the DRC on issues such as urbanization, the objective of the study is to provide Chinese policy makers with detailed institutional and policy options to support water security in the country. This study fills a critical gap highlighted in the World Bank 2013 China Country Water Resources Assistance Strategy by proposing legal, technical, and institutional changes to the current framework for water resource management. A new water governance approach is recommended that aims to balance economic growth with increasing water demand under conditions of water scarcity. By closely examining key water management issues in the context of China's rapid development, the study also aims to provide lessons relevant to other low- and middle-income countries facing similar water-related challenges. The report identifies five priority areas for reform: 1) Enhance the legislative foundation for water governance; 2) Strengthen national and basin-level water governance; 3) Improve and optimize economic policy instruments; 4) Strengthen adaptive capacity to climate and environmental change; and 5) Improve data collection and information-sharing.